Learning Discipline and Student Ethics on Learning Outcomes - Hendrisman, Hendrisman; Yuhasnil, Yuhasnil (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
The aim of this research is to describe Contribution of learning discipline and student ethics to the learning outcomes of class VIII students at SMPN 7 Pakumbuh . This type of research is quantitative research using the correlation method. The population in this study was 108 people with a sample of 20 students . The sampling technique is carried out by determining the class that will be sampled ( Cluster Sample ). Discipline and ethics data were obtained from questionnaires that had been filled in by students and learning outcome data were obtained from the homeroom teacher. The results of data analysis show that: (1) learning disciplines contribute 63% to the learning outcomes of class VIII students at SMPN 7 Payakumbuh. (2) Student ethics contributes 75.1% to the learning outcomes of class VIII students at SMPN 7 Payakumbuh. (3) Student learning discipline and ethics contribute 77% to the learning outcomes of class VIII students at SMPN 7 Payakumbuh. The conclusion is that learning discipline and student ethics contribute to Indonesian language learning outcomes.